Flexible large-area organic tandem solar cells with high defect tolerance and device yield. Issue 7 (2nd February 2017) - Mao, Lin; Tong, Jinhui; Xiong, Sixing; Jiang, Fangyuan; Qin, Fei; Meng, Wei; Luo, Bangwu; Liu, Yun; Li, Zaifang; Jiang, Youyu; Fuentes-Hernandez, Canek; Kippelen, Bernard; et al.
Abstract : Tandem structures have higher defect tolerance than single-junction. 10.5 cm 2 flexible tandem solar cells yielding a PCE of 6.5%. Abstract : The fabrication of thin layers of organic photoactive materials (typically ca. 100–200 nm thick) over large area is needed for the commercial realization of organic solar cells. This is challenging because defects on these thin layers can cause high leakage currents which lead to poor device performance and, ultimately, to poor device yield. Here, we report that organic solar cells with a tandem structure can display an increased tolerance to defects and are found less susceptible to parasitic area scaling-up effects compared to single-junction solar cells. We demonstrate 10.5 cm 2 flexible tandem solar cells with a power conversion efficiency of 6.5% with a fabrication yield of over 90% in a laboratory environment. The high fabrication yield and good performance displayed by tandem organic solar cells suggest that despite their increased complexity, they could provide a viable path towards the commercial realization of efficient large-area organic solar cells.